Atraumatic Anterior Hip Dislocation as High Grade of Hip Instability: A Case Report. Issue 2 (April 2021) - Arbeloa-Gutierrez, Lucas; Arenas-Miquelez, Antonio
Abstract : Case: Fifty-year-old woman who presented an atraumatic anterior hip dislocation during a local traditional dance exhibition. The dislocation occurred during a dance step in which extreme hip position in extension and external rotation was held. After urgent closed reduction under general anesthesia, the patient underwent conservative management with a follow-up of 24 months. There were no further dislocation events or sequelae, with the Hip Disability and Osteoarthritis Outcome Score-12 scale score was 100 points at the end of follow-up. Conclusions: Atraumatic hip dislocation is the highest grade and exceptional presentation of hip instability and requires immediate treatment. Conservative treatment is satisfactory, although in case of recurrence or persistent residual symptoms, other treatments are warrant.